Exchange rate behaviour and management in Malaysia: empirical study across regimes / Azlul Kalilah Zaghlol - Zaghlol, Azlul Kalilah (Institute of Graduate Studies, UiTM, 2017)
economic developments, a study on exchange rate behaviour becomes crucial for the economic stability and achievement of macroeconomic objectives. There have been claims that fixed exchange rate regime is more prone to overvaluation and responsible for devastating currency crises. However, empirical studies on exchange rate behaviour do not seem to have established whether currency misalignment and the regime choice are the ones potentially responsible. This study thus examines the behaviour of exchange rates and its management given the unique experience in Malaysia during the 1997 financial crisis. Firstly, its objective is to measure real exchange rate misalignment (RERMIS) upon estimation of its equilibrium level. Secondly, this study tests the Fixed Exchange Rate Regime-Misalignment (FERRM) hypothesis in establishing whether the pegged regime contributed to the worsening of misalignment. The third objective looks into the exchange market pressure (EMP) and its associated intervention. It answers the question of “deliberateness” with regard to exchange rate management policy, specifically whether it is a resulting behaviour of deliberate action or merely due to the market forces.